Toward a Method for Safety and Security Requirements Alignment in Critical IoT Systems - Veiga, Ernesto Fonseca; Bulcão-Neto, Renato de Freitas (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
The complexity of critical IoT systems demands the joint treatment of safety and security requirements from the early system life cycle stages. Dealing with multiple (and sometimes conflicting) relationships between such requirements has been a great research need. We present a preliminary version of a method for the alignment of safety and security requirements for critical IoT systems based on the System Theoretic Process Analysis (STPA) technique. A simple use case of our method shows how those requirements are handled during the conception and elicitation phases. When fully defined, our method will help analysts handle safety and security as first-class concerns from conception to specification of critical IoT systems, including requirements dependencies and conflicts.